PENGARUH HARGA, KETEPATAN WAKTU PENGIRIMAN, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA JASA PENGIRIMAN BARANG DI JNE (STUDI KASUS PADA PT. JNE KATAMSO MEDAN) - SARTIKA .; LUSIAH .; RIPKA SERIIDAHNAITA GINTING (LP2MTBM MAKARIOZ, 2022)
This research aims to find out the effect of price, timeliness of delivery and quality of service on consumer loyalty to deliveryservices at JNE. The method used is quantitative method. The types of data used are primary data and secondary data. Thepopulation in this study was consumers who had used delivery services at JNE at least 2 times and consumers who workedas self-employed who owned an online shop and chose their delivery services through JNE. Sampling method usingNonprobability Sampling and sampling technique using Incidental Sampling using Purba Rao formula. The sample numberused as many as 96 respondents with a significance level of 5% using SPPS version 17.0. Data analysis techniques used forvalidity and reliability tests, classical assumption tests, multicollinearity tests, heteroskedasticity tests, partial tests (t tests),simultaneous tests (F), multiple linear regression analysis and coefficients of determination (R2). The results showed thatpartially the price had a positive and significant effect on consumer loyalty to JNE Katamso Medan. This is seen from theresults of the partial test (Test t) where the thitung value> is 4.872 > 1.98489. Partially, the timeliness of delivery positivelyand significantly affects consumer loyalty to JNE Katamso Medan. This is seen from the results of the partial test (Test t)where the value of thitung> ttabel is 5.169 > 1.98489. Partially the quality of service positively and significantly affectsconsumer loyalty to JNE Katamso Medan. This is seen from the results of the partial test (Test t) where the thitung value> is2.768 > 1.98489. From the results of the test there is an effect on price, timeliness of delivery and quality of service toconsumer loyalty to delivery services at JNE Katamso Medan.